Perkaitan di antara faktor-faktor tekanan dengan keselamatan di tempat kerja - Wati, Kuching. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Generally, this study aims to identify the relationship between stress factors with safety in the workplace. The independent variables for this study were job condition, job environment, social interaction and organization culture. Meanwhile, the dependent variable was safety in the workplace. 58 supporting staffs from Dewan Bandaraya Kuching Utara (DBKU) were selected as a sample for this study. Questionnaire was used for collecting data. Statistical tests carried out were the One Way ANOVA, Independent Sample t-test, Pearson Correlation Analysis and Linear Regression Analysis. The results showed that there was a significant relationship between all stress factors (job condition, job environment, social interaction and organization culture) with safety in the workplace. From Linear Regression Analysis, the results revealed that job condition was the dominant factor influencing safety in the workplace. As a conclusion, this study shows that stress factors have a strong relationship with safety in the workplace and should be given serious attention by organization.